Ionic liquids for the synthesis of metal nanoparticles. Issue 6 (22nd April 2013) - Richter, Kai; Campbell, Paul S.; Baecker, Tobias; Schimitzek, Agnes; Yaprak, Damla; Mudring, Anja‐Verena
Abstract Ionic liquids (ILs) offer outstanding possibilities as media for manufacturing nanoparticles. Synthesis conditions with high reaction and nucleation rates are achievable leading to the formation of extremely small particles. The IL itself can act as an electronic as well as a steric stabiliser preventing particle growth and particle aggregation. In addition, as highly structured liquids, ILs have a strong effect on the morphology of the particles formed. We have developed two synthesis techniques for the generation of metal nanoparticles that take advantage of the unique properties that ILs offer when compared to conventional volatile organic solvents (VOCs): microwave (MW) synthesis and physical vapour deposition (PVD). The ionic character and high polarisability of the IL renders it highly susceptible to energy uptake via MWs and extreme heating and reaction rates can be achieved. To make full use of the possibilities that ILs offer we have designed a set of reducing ILs which can be used as direct reaction partners for the generation of metal nanoparticles. The negligible vapour pressure of many ILs makes experiments under high vacuum possible and allows for the PVD of metals into ILs. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text> Physical vapour deposition (left) and microwave synthesis of metal nanoparticles in ILs.